182k views
5 votes
Solve 3x^3-9x^2-12x

User Vascop
by
6.1k points

1 Answer

7 votes

Answer:

x = -1, 0, and 4

Explanation:

Step 1: Set the expression equal to zero. Solving means to find out what values of x make the equation equal zero.

3x³ - 9x² - 12x = 0

Step 2: Factor out the largest common factor is there is one.

Here the largest common factor is 3x. Now we have

3x(x² - 3x - 4) = 0

Step 3: Factor the quadratic expression x² - 3x - 4

3x(x - 4)(x + 1) = 0 (two numbers that add up to -3 and multiply to -4)

Step 4: Set each term equal to zero and solve..

3x = 0, so x = 0 (divide both sides by 3 to isolate x)

x - 4 = 0, so x = 4 (add 4 to both sides to isolate x)

x + 1 = 0, so x = -1 (subtract 1 from both sides to isolate x)

So our solutions are

x = -1, 0, and 4

User Johalternate
by
6.3k points